Analisis Strategi Kampanye Calon Anggota Legislatif Marcu Buana Mba’u dari Partai Nasional Demokrat dalam Pileg 2024 Kabupaten Timor Tengah Selatan - Geral Alvander Tode (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This research aims to analyze the campaign strategy used by Marcu Buana Mba’u, a legislative candidate from the National Democrat Party (NasDem), in the 2024 election in South Central Timor (TTS). The research was conducted in Tuasene Village using qualitative methods, including interviews, observation, and documentation. The findings reveal that Marcu Buana Mba’u’s campaign emphasized a defensive strategy, capitalizing on his previous track record, trust from constituents, and tangible results such as infrastructure development. This strategy contributed significantly to his re-election. The analysis uses Peter Schroder’s political strategy theory to distinguish between offensive and defensive approaches.